A feasibility study Cleaners on 'd go - Claridad, Ma. Lourdes Bernadette V. (College of Engineering, 2002)
Cleaners on 'd Go is a partnership venture which offers home cleaning and gardening services. It will cater to the house cleaning and gardening needs of the middle class households in Quezon City. From the market study, the market demand was projected to be steadily increasing from 2003 to 2007. The company will be adapting an aggressive type of outdoor advertising which includes panaflex signs, roving van, and distribution of pamphlets, flyers and posters. the total marketing budget amounted to PhP 960,100 for a period of five years. In the technical study of Cleaners on 'd Go, the service blueprint, service manual, and standard operating procedures were established. Chemical cleaning agents and equipment suppliers were determined using the Weighted-Criteria Method. The labor requirement of the company was also determined. It consists of one general manager, one administrative assistant, three drivers, four Supervisors, four gardeners, 16 cleaners. Scheduling employee days-off and van development were also done. Lastly, the specific location of Cleaners on 'd Go was determined to be in 68 Carba Bldg., West Avenue, Quezon City. In the financial study, the Projected Income Statement of Cleaners on 'd Go for the years 2003-2007 reflects its profitability. The resulting net incomes for the five year study period were steadily increasing. Moreover, the Statement of Cash Flows shows that the company is able to generate sufficient cash throughout the five year period. The current ratio, fixed assets-to-net worth ratio, return on assets, and payback period also yielded positive results that further supports the financial viability of Cleaners on 'd Go. Based on the market, technical, organization & management, financial, and social profitability studies done, it was concluded that establishing and operating Cleaners on 'd Go is FEASIBLE.